ACCURACY AND SAFETY OF BIS MONITORING USING A NOVEL INTERFACE DEVICE CONNECTING CONVENTIONAL NEEDLE ELECTRODES AND BIS SENSORS FOR FOREHEAD SURGICAL APPROACH - Harada, Hideki; Tauchi, Miyuki (ANESTHESIA AND ANALGESIA, 2019)
CRIS-Team WoS Importer:2021-10-18

Accuracy of BIS monitoring using a novel interface device connecting conventional needle-electrodes and BIS sensors during frontal neurosurgical procedures - Harada, Hideki; Muta, Seiya; Kakuma, Tatsuyuki; Ukeda, Misa; Ota, So; Hirata, Maiko; Fujioka, Hiroshi; Nakashima, Osamu; Dietel, Barbara; Tauchi, Miyuki (PLoS ONE, 2021)
Background Bispectral index (BIS) monitoring is a widely used non-invasive method to monitor the depth of anesthesia. However, in the event of surgeries requiring a frontal approach, placement of the electrode may be impossible at the designated area to achieve a proper BIS measurement. Methods We developed an investigational interface device to connect needle-electrodes to BIS sensors. The safety and clinical performance were investigated in patients who underwent surgery. Direct BIS values from a disposable BIS electrode and indirect values via the interface device were simultaneously recorded from the same areas of electrode placement in a single patient. The agreement between the direct and indirect BIS values was statistically analyzed. Results The interface device with a silver electrode demonstrated sufficient electric conduction to transmit electroencephalogram signals. The overall BIS curves were similar to those of direct BIS monitoring. Direct and indirect BIS values from 18 patients were statistically analyzed using a linear mixed model and a significant concordance was confirmed (indirect BIS = 7.0405 + 0.8286 ∗ direct BIS, p<0.0001). Most observed data (2582/2787 data points, 92.64%) had BIS unit differences of 10 or less. Conclusions The interface device provides an opportunity for intraoperative BIS monitoring of patients, whose clinical situation does not permit the placement of conventional adhesive sensors at the standard location.
CRIS-Team Scopus Importer:2021-11-05

ALTERATION OF CONNEXIN EXPRESSION DURING EARLY STAGE OF ATHEROSCLEROSIS - Oshita, Kensuke; Urschel, K.; Botos, B.; Achenbach, Stephan; Dietel, B.; Tauchi-Brück, Miyuki (ATHEROSCLEROSIS, 2021)
CRIS-Team WoS Importer:2021-09-24

DECREASING GPLD 1-LEVELS IN PATIENTS AFTER ST-ELEVATED MYOCARDIAL INFARCTION - Kruse, A.; Bischof, Erik; Raaz-Schrauder, D.; Achenbach, Susanne; Dietel, B.; Tauchi, Miyuki; Urschel, K. (ATHEROSCLEROSIS, 2022)
CRIS-Team WoS Importer:2022-10-14

Formation of atherosclerotic lesions is independent of eosinophils in male mice - Hofheinz, Katharina; Seibert, Fabian; Ackermann, Jochen; Dietel, Barbara; Tauchi, Miyuki; Oszvar-Kozma, Maria; Kühn, Hartmut; Schett, Georg; Binder, Christoph J.; Krönke, Gerhard (Atherosclerosis, 2020)
Background and aims: Oxidation of low-density lipoprotein (LDL) and oxidized LDL-mediated activation of the innate immune system have been recognized as early key events during the pathogenesis of atherosclerosis. Recent evidence identified eosinophils as a major source of enzymatic lipid oxidation and suggested a potential role of type 2 immunity in atherogenesis. However, the involvement of individual type 2 immune cell subsets involved in this process has been incompletely defined. We therefore sought to determine the role of eosinophils during LDL oxidation and the pathogenesis of this disease. Methods: Using eosinophil-deficient dblGATA1 mice, we studied the role of eosinophils in two established mouse models of atherosclerosis. Results: These experiments revealed that the presence of eosinophils did neither affect biomarkers of LDL oxidation nor atherosclerotic lesion development. Conclusions: The obtained results show that LDL oxidation and development of atherosclerosis are largely independent of eosinophils or eosinophil-mediated LDL oxidation.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Atherosclerosis; Eosinophils; Lipid oxidation

Investigation of wall shear stress in cardiovascular research and in clinical practice—from bench to bedside - Urschel, Katharina; Tauchi, Miyuki; Achenbach, Stephan; Dietel, Barbara (International Journal of Molecular Sciences, 2021)
In the 1900s, researchers established animal models experimentally to induce atherosclerosis by feeding them with a cholesterol-rich diet. It is now accepted that high circulating cholesterol is one of the main causes of atherosclerosis; however, plaque localization cannot be explained solely by hyperlipidemia. A tremendous amount of studies has demonstrated that hemodynamic forces modify endothelial athero-susceptibility phenotypes. Endothelial cells possess mechanosensors on the apical surface to detect a blood stream-induced force on the vessel wall, known as “wall shear stress (WSS)”, and induce cellular and molecular responses. Investigations to elucidate the mechanisms of this process are on-going: on the one hand, hemodynamics in complex vessel systems have been described in detail, owing to the recent progress in imaging and computational techniques. On the other hand, investigations using unique in vitro chamber systems with various flow applications have enhanced the understanding of WSS-induced changes in endothelial cell function and the involvement of the glycocalyx, the apical surface layer of endothelial cells, in this process. In the clinical setting, attempts have been made to measure WSS and/or glycocalyx degradation non-invasively, for the purpose of their diagnostic utilization. An increasing body of evidence shows that WSS, as well as serum glycocalyx components, can serve as a predicting factor for atherosclerosis development and, most importantly, for the rupture of plaques in patients with high risk of coronary heart disease.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Atherosclerosis; Endothelial activation; Glycocalyx; Mechanotrans-duction; Plaque; Rupture; Wall shear stress

SERUM IL-6 CONCENTRATION CORRELATES WITH PLAQUE VULNERABILITY AND RUPTURE IN PATIENTS WITH SEVERE CAROTID STENOSIS - Dietel, B.; Urschel, K.; Tauchi, Miyuki; Achenbach, Susanne (ATHEROSCLEROSIS, 2022)
CRIS-Team WoS Importer:2022-10-14

Soluble CD83 improves and accelerates wound healing by the induction of pro-resolving macrophages - Royzman, Dmytro; Peckert-Maier, Katrin; Stich, Lena; König, Christina; Wild, Andreas; Tauchi, Miyuki; Ostalecki, Christian; Kiesewetter, Franklin; Seyferth, Stefan; Lee, Geoffrey; Eming, Sabine A.; Fuchs, Maximilian; et al. (Frontiers in Immunology, 2022)
To facilitate the recovery process of chronic and hard-to-heal wounds novel pro-resolving treatment options are urgently needed. We investigated the pro-regenerative properties of soluble CD83 (sCD83) on cutaneous wound healing, where sCD83 accelerated wound healing not only after systemic but also after topical application, which is of high therapeutic interest. Cytokine profile analyses revealed an initial upregulation of inflammatory mediators such as TNFα and IL-1β, followed by a switch towards pro-resolving factors, including YM-1 and IL-10, both expressed by tissue repair macrophages. These cells are known to mediate resolution of inflammation and stimulate wound healing processes by secretion of growth factors such as epidermal growth factor (EGF) and vascular endothelial growth factor (VEGF), which promote vascularization as well as fibroblast and keratinocyte differentiation. In conclusion, we have found strong wound healing capacities of sCD83 beyond the previously described role in transplantation and autoimmunity. This makes sCD83 a promising candidate for the treatment of chronic- and hard-to-heal wounds.
CRIS-Team Scopus Importer:2022-10-28
Keywords: CD83; macrophages; stem cells; therapy; tissue regeneration; wound healing

The Involvement of Cx43 in JNK1/2-Mediated Endothelial Mechanotransduction and Human Plaque Progression - Tauchi, Miyuki; Oshita, Kensuke; Urschel, Katharina; Furtmair, Roman; Kühn, Constanze; Stumpfe, Florian; Botos, Balazs; Achenbach, Stephan; Dietel, Barbara (International Journal of Molecular Sciences, 2023)
Atherosclerotic lesions preferentially develop at bifurcations, characterized by non-uniform shear stress (SS). The aim of this study was to investigate SS-induced endothelial activation, focusing on stress-regulated mitogen-activated protein kinases (MAPK) and downstream signaling, and its relation to gap junction proteins, Connexins (Cxs). Human umbilical vein endothelial cells were exposed to flow (“mechanical stimulation”) and stimulated with TNF-α (“inflammatory stimulation”). Phosphorylated levels of MAPKs (c-Jun N-terminal kinase (JNK1/2), extracellular signal-regulated kinase (ERK), and p38 kinase (p38K)) were quantified by flow cytometry, showing the activation of JNK1/2 and ERK. THP-1 cell adhesion under non-uniform SS was suppressed by the inhibition of JNK1/2, not of ERK. Immunofluorescence staining and quantitative real-time PCR demonstrated an induction of c-Jun and c-Fos and of Cx43 in endothelial cells by non-uniform SS, and the latter was abolished by JNK1/2 inhibition. Furthermore, plaque inflammation was analyzed in human carotid plaques (n = 40) using immunohistochemistry and quanti-gene RNA-assays, revealing elevated Cx43+ cell counts in vulnerable compared to stable plaques. Cx43+ cell burden in the plaque shoulder correlated with intraplaque neovascularization and lipid core size, while an inverse correlation was observed with fibrous cap thickness. Our results constitute the first report that JNK1/2 mediates Cx43 mechanoinduction in endothelial cells by atheroprone shear stress and that Cx43 is expressed in human carotid plaques. The correlation of Cx43+ cell counts with markers of plaque vulnerability implies its contribution to plaque progression.
CRIS-Team Scopus Importer:2023-02-03
Keywords: atherogenesis; endothelial dysfunction; gap junctions; MAPK; mechanotransduction; shear stress

The Shear Stress–Regulated Expression of Glypican-4 in Endothelial Dysfunction In Vitro and Its Clinical Significance in Atherosclerosis - Urschel, Katharina; Hug, Karsten; Zuo, Hanxiao; Büttner, Michael; Furtmair, Roman; Kühn, Constanze; Stumpfe, Florian; Botos, Balaz; Achenbach, Stephan; Yuan, Yan; Dietel-Schor, Barbara; Tauchi-Brück, Miyuki (International Journal of Molecular Sciences, 2023)
Retention of circulating lipoproteins by their interaction with extracellular matrix molecules has been suggested as an underlying mechanism for atherosclerosis. We investigated the role of glypican-4 (GPC4), a heparan sulfate (HS) proteoglycan, in the development of endothelial dysfunction and plaque progression; Expression of GPC4 and HS was investigated in human umbilical vein/artery endothelial cells (HUVECs/HUAECs) using flow cytometry, qPCR, and immunofluorescent staining. Leukocyte adhesion was determined in HUVECs in bifurcation chamber slides under dynamic flow. The association between the degree of inflammation and GPC4, HS, and syndecan-4 expressions was analyzed in human carotid plaques; GPC4 was expressed in HUVECs/HUAECs. In HUVECs, GPC4 protein expression was higher in laminar than in non-uniform shear stress regions after a 1-day or 10-day flow (p < 0.01 each). The HS expression was higher under laminar flow after a 1 day (p < 0.001). Monocytic THP-1 cell adhesion to HUVECs was facilitated by GPC4 knock-down (p < 0.001) without affecting adhesion molecule expression. GPC4 and HS expression was lower in more-inflamed than in less-inflamed plaque shoulders (p < 0.05, each), especially in vulnerable plaque sections; Reduced expression of GPC4 was associated with atherogenic conditions, suggesting the involvement of GPC4 in both early and advanced stages of atherosclerosis.
CRIS-Team Scopus Importer:2023-08-11
Keywords: atherosclerosis; endothelial dysfunction; glypican-4; heparan sulfate; plaque; sex differences; shear stress